Response of Different Levels of Nitrogen Fertilizer and Water Stress on the Growth and Yield of Japanese Mint (Mentha Arvensis L.) (Bangladesh Journal of Scientific and Industrial Research, 2009)
The response of mint (Mentha arvensis L.) to different levels of nitrogen and different levels of water stress were investigated. Relative performances of different growth and yield parameters such as plant height and fresh weight of shoot as influenced by N-fertilizer and water stress were investigated. Pot experiment was conducted with five levels of N treatments- 0, 60, 120, 180, and 240 kg N ha-1 and four levels of water conditions 100, 75%, 50 and 25% field capacity. Plant growth (height and fresh herb (product) was affected by water stress and different N levels. At 100% field capacity, the highest dose of N- (240kg N/ha) Produced maximum plant height (46.33 cm) and fresh herb product. Lower dose of N treatment decreased the plant height and herb product. Compared to 100% field capacity the fresh herb product was drastically decreased from 103.54 -31.67 g pot -1 at 25% field capacity. Key words: Mentha arvensis, Water stress, N-fertilization, Yield of mint.   doi: 10.3329/bjsir.v44i1.2723 Bangladesh J. Sci. Ind. Res. 44(1), 137-145, 2009